Translation methods applied to translate Polish types and names of administrative law authority bodies into English – a case study - Kizińska, Anna (Językoznawstwo, 2023)
The paper aims to discuss Polish terms that name authority bodies under the administrative law and their English equivalents. The Polish terms under analysis appear in the first Division of the Polish Code of Administrative Procedure of 14 June 1960 and the English equivalents of each Polish term researched have been suggested in the Polish Code of Administrative Procedure translation into English. The research problem is to determine the translation methods applied and to verify whether translation methods used in the Polish-English translation of the above terms which have been determined as culture-specific items appear among translation methods applied when translating culture-specific elements suggested by Hejwowski (2007). Furthermore, to verify whether the mentioned translation methods appear among the translation methods discussed by Weston (1993) which are recommended to be applied while translating legal terms. The theoretical part of the paper includes a presentation of the definitions of a legal term, culture-specific item and the classification of translation methods by Hejwowski and Weston. The research stages include the comparison of definitions of source elements and definitions of their equivalents, as long as they appear in monolingual English law dictionaries.